The Effectiveness of Acting Play Script Technique Towards Students’ Speaking Ability at Tenth Year of SMAN I Lambuya - umar, umar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigated The Effectiveness Of Acting Play Script Technique towards Students’ Speaking Ability At Tenth Year Of SMAN I Lambuya. The research question of this study adressed “Does the Acting Play Script Technique have significant effect towards students’ speaking ability?